2008
DOI: 10.1097/aog.0b013e31817c4ea7
|View full text |Cite
|
Sign up to set email alerts
|

Fascioliasis in Pregnancy

Abstract: Fascioliasis often mimics another common problem in pregnancy, cholelithiasis; clinicians need to be aware of this disease in high-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
(14 reference statements)
0
5
0
1
Order By: Relevance
“…In Mexico, although human infection appears also sporadically reported in recent years [54] – [59] , various aspects clearly suggest that the disease should be considered a national health concern: (i) human cases have been reported from several states other than Puebla, such as Hidalgo, Mexico, Veracruz, Chiapas, Oaxaca, San Luis-Potosi, Jalisco and Morelos [23] ; (ii) massively infected patients have been diagnosed [60] ; (iii) children have been found to be infected in surveys in Chiapas [61] and Mexico city [62] ; and (iv) several of the patients recently diagnosed in Canada and the United States were in fact immigrants from Mexico [63] [67] . Prevalences and intensities found in the present study in Atlixco municipality are the highest so far recorded in the country and add thus concern about the possible level of human fascioliasis underestimation countrywide.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, although human infection appears also sporadically reported in recent years [54] – [59] , various aspects clearly suggest that the disease should be considered a national health concern: (i) human cases have been reported from several states other than Puebla, such as Hidalgo, Mexico, Veracruz, Chiapas, Oaxaca, San Luis-Potosi, Jalisco and Morelos [23] ; (ii) massively infected patients have been diagnosed [60] ; (iii) children have been found to be infected in surveys in Chiapas [61] and Mexico city [62] ; and (iv) several of the patients recently diagnosed in Canada and the United States were in fact immigrants from Mexico [63] [67] . Prevalences and intensities found in the present study in Atlixco municipality are the highest so far recorded in the country and add thus concern about the possible level of human fascioliasis underestimation countrywide.…”
Section: Discussionmentioning
confidence: 99%
“…Fascioliasis is one of the most debilitating zoonotic diseases of domestic herbivores and human beings (Ashrafi et al 2006;WHO 2006;Lewin 2007;Alatoom et al 2008). Earlier, fascioliasis was limited to populations within well-defined watershed boundaries: however; recent environmental changes and modification in human behavior have increased the risk in other new populations (Savioli et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…On the clinical epidemiologial aspects showed that in pregnant women with fascioliasis, symptoms and signs are indistinguishable from hepatobiliary, digestive tract diseases or overlap with gestation terrains, and clinical signs of paediatric fascioliasis may mimic a wide spectrum of hepatobiliary disorders. Particularly, the combination of clinical pictures, laboratory finding parameters and imaging diagnostics, especially in FasELISA, hypereosinophilia and liver lesions by ultrasound and MRI or MDCT (in special cases) were very useful in definitive and confirmed diagnosis [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%